Optimal Location and Parameter Setting of STATCOM Device Based PSO for Iraqi Grid Voltage Profile Enhancement and Power Losses Minimizing - Rashid Al-Rubayi; Mohammed Eesee (Engineering and Technology Journal, 2019)
The main goal of this work is to enhance the Voltage stability by using optimum location and parameters setting of STATCOM device. The parameters are the magnitude of the output voltage 𝑉𝑉𝑅 and the angle 𝛿𝑉𝑅, these parameters are taken to control the device performance. The simulation results have been done by using power flow program solution by Newton-Raphson method (Matlab program / M-file) with Particle Swarm Optimization (PSO) technique, for power losses minimizing and improving voltage profile. Two systems have been implemented:- IEEE 5-bus test system and Iraqi (400 kV) National super Grid System 27-bus. The MATLAB programs are Applied in the first step on IEEE 5- bus test system to examine the performance of the programs by comparing the results with other references, then it is implemented on Iraqi (400 kV) National super Grid System to find optimum location and parameter setting of STATCOM device. The results show that, the STATCOM has significant effect on improving the voltage profile and reducing apparent power losses, The STATCOM device performance depends on its location and parameter settings, and The PSO algorithm can easily find out the optimal location and parameters setting of the STATCOM for which the voltage deviation are minimum